Chronic exertional compartment syndrome of the foot. Issue 2 (20th January 2011) - Padhiar, N; Tardioli, A; Allen, M; King, J B
Abstract : In this paper the authors present a case history along with results of case series and a literature review to demonstrate the complexity of this condition. The main aim is to increase the awareness among clinicians and the scientist to research in the area of chronic exertional compartment syndrome (CECS). CECS usually refers to myoneural ischaemia due to a reversible increase in tissue pressure within a myofascial compartment. CECS of the leg is well documented in the literature since it was first described by Mavor in 1956. CECS of the foot remains underdiagnosed and has been reported in the literature only on an anecdotal basis. Wood Jones proposed that there were four compartments in the foot but Manoli and Weber suggest that there are nine separate muscle compartments. Clinical signs and symptoms of CECS of the foot remain diverse and lack the consistency of its counter part in the leg. The range of signs and symptoms include swelling, tension, cramps, tightness, paraesthesia, numbness, cyanosis and soft tissue indurations. As a result number of diagnosis is first considered and includes plantar fasciitis, tibialis posterior tendonitis, tarsal tunnel syndrome and medial Lisfranc injury. CECS of the foot remains a diagnosis of exclusion. The most effective treatment is a superficial fasciotomy.